A Study of volumetric variations of basal nuclei in the normal human brain by magnetic resonance imaging. Issue 2 (12th January 2017) - Elkattan, Amal; Mahdy, Amal; Eltomey, Mohamed; Ismail, Radwa
Abstract : Knowledge of the effects of healthy aging on brain structures is necessary to identify abnormal changes due to diseases. Many studies have demonstrated age‐related volume changes in the brain using MRI. 60 healthy individuals who had normal MRI aged from 20 years to 80 years were examined and classified into three groups: Group I: 21 persons; nine males and 12 females aging between 20‐39 years old. Group II: 22 persons; 11 males and 11 females aging between 40‐59 years old. Group III: 17 persons; eight males and nine females aging between 60‐80 years old. Volumetric analysis was done to evaluate the effect of age, gender and hemispheric difference in the caudate and putamen by the slicer 4.3.3.1 software using 3D T1‐weighted images. Data were analyzed by student's unpaired t test, ANOVA and regression analysis. The volumes of the measured and corrected caudate nuclei and putamen significantly decreased with aging in males. There was a statistically insignificant relation between the age and the volume of the measured caudate nuclei and putamen in females but there was a statistically significant relation between the age and the corrected caudate nuclei and putamen. There was no significant difference on the caudate and putamen volumes between males and females. There was no significant difference between the right and left caudate nuclei volumes. There was a leftward asymmetry in the putamen volumes. The results can be considered as a base to track individual changes with time (aging and CNS diseases). Clin. Anat. 30:175–182, 2017. © 2017 Wiley Periodicals, Inc.